Reconstructing Histories. Mapping Artists’ Film and Video on Channel 4 through Archival Ruination (1982-1992) - Atkinson, Nicole (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
This paper examines how archival research is integral in order to reconstruct the forgotten history of Channel 4’s involvement and support of artists’ moving image and independent film and video production in the UK between 1982-1992. As a broadcaster formed and operating under a unique publisher-broadcaster model, the channel does not archive its programming materials, meaning much of this history is left in a state of archival ruination. Examination of collections and counter-archives provide essential and overlooked insights into this largely eradicated history. These archives challenge the conventional hierarchies of institutional memory and highlight the importance of preserving marginalised voices and practices. By examining three pertinent archives containing fragments of the overlooked history of artists’ moving image on Channel 4, this paper underscores the methodological challenges of working with the ruination of disparate archives, including issues of access, fragmentation, and the subjectivity of archival curation. It works to propose the need for a pluralistic approach to archival research for neglected broadcast histories.